Synthesis of Powdered [Mn(bipy)3](CF3SO3)2·5.5H2O: The Physical Properties and Antibacterial Activity - Kristian Handoyo Sugiyarto; Dwi Anggi Marini; Hari Sutrisno; Dyah Purwaningsih; Cahyorini Kusumawardani (Indonesian Journal of Chemistry, 2023)
The synthesis of the complex containing manganese(II), bipyridine (bipy) as a ligand, and an anionic trifluoromethane sulfonate (triflate) is reported. The corresponding metal content, conductance, and DTG-TGA of the complex lead to the formula of [Mn(bipy)3](triflate)2·5.5H2O. The fully high-spin magnetic moment is observed, corresponding to five unpaired electrons in the metal ion. The electronic spectral bands suggest the three possible spin-forbidden transitions of the sextet to quartet states. The mode of vibrations of the IR spectrum supports the typical ring of bipy, and the triflate. The images of SEM-EDX indicate the presence of the corresponding elemental content and reflect the relatively high crystallinity, as it is evidenced in the profile of the corresponding powdered diffractogram. The refinement of powdered XRD following the Le Bail program suggests being structurally triclinic symmetry of P21/c. This complex shows inhibition of bacterial activity against S. aureus and E. coli.